Effects of pelleting and pellet conditioning temperatures on weanling pig performance - Steidinger, M.U.; Tokach, Michael D.; O'Quinn, P.R.; Woodworth, J.C.; McKinney, Leland J.; Borg, B.S.; Campbell, J.M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies were conducted to evaluate" the effects of pelleting and pellet conditioning temperature of diets containing 5% spray-dried animal plasma (SDAP) on weanling pig growth performance. In Exp. 1, conditioning temperatures evaluated were 140, 150, 160, and 170°F. In Exp. 2, pellet conditioning temperatures were 140, 155, 170, 185, and 200°F. The results suggest that pellet conditioning temperatures above 170°F decrease weanling pig performance from d 0 to 7 after weaning. Pellet conditioning temperature should not exceed 170OF (exit temperature of 180°F) for nursery diets containing 5% SDAP.
Keywords: Swine; Weanling pigs; Spray-dried animal plasma; Pellet conditioning termperature